Peran Gembala Dalam Membentuk Karakter Spiritualitas Remaja Kristen - Hendrikson Febri (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The spiritual character of Christian adolescents is crucial to develop in today's context. Many incidents indicate that Christian teenagers often neglect their spiritual character; nearly 60% of them do not participate in worship, which hinders their spiritual development. This research aims to provide solutions for pastors in shaping the spiritual character of Christian adolescents. The study employs a qualitative research method involving analysis of textbooks, articles, and other sources. The significant role of pastors in shaping the spiritual character of today's Christian youth is emphasized. The findings and discussions underscore that pastors, in fostering spiritual character among Christian adolescents, should embody divine attributes such as love, patience, justice, and strength. This approach ensures effective and proper character formation.